Materials of scientific and practical conference «Dietoogy In Practice Of Endocrinologist» at the VIII (XXV) Russian Diabetology Congress With International Participation «Diabetes Mellitus – XXIth Century Pandemia» - Marina V. Shestakova; Lyudmila A. Ruyatkina; Lyudmila A. Suplotova; Svetlana A. Smetanina; Elena B. Khramova; Natalia Y. Arbatskaya; Liudmila I. Ibragimova; Irina S. Iskhakova; Zukhra S. Pavlova; Alla V. Shilina; Fatima H. Dzgoeva; Minara S. Shamkhalova (Ожирение и метаболизм, 2019)
The scientific-practical conference Dietoogy In Practice Of Endocrinologist was held during the VIII Russian diabetology congress with international participation “Diabetes Mellitus – XXIth Century Pandemia”. It was chaired by Academician of RAS M.V. Shestakova (Moscow), Professors L.A. Ruyatkina (Novosibirsk ) and L.A. Suplotova (Tyumen). The expediency of this event was dictated by the necessity to create a unified national regulated guidelines for the diet therapy of obesity and associated diseases for the medical community and patients. The program of the meeting included a discussion about the formation of a healthy diet and its effect on the body, starting from the pregnant women, fetal development, the breastfeeding period, in the period of perimenopause and postmenopause, in the presence of concomitant pathology of heart and kidneys.